(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
this article thoroughly analyzes the aesthetic attitude of the phenomenon of ecological consciousness and culture of an individual to nature, the main functions of eco esthetic thinking, as well as the functional role of the ecological consciousness of an individual, which consists in organizing, managing and controlling nature through the formation of an aesthetic attitude to nature.